METAPHOR IN THE METALANGUAGE OF LINGUISTICS: BASED ON THE MATERIAL OF THE ENGLISH LANGUAGE - Shukhratova Mukhlisakhon Shukhratjon qizi (Scholar Express Journal, 2022)
Any science at a certain stage of its development is characterized by in-depth metascientific reflection, addressed to the problems of its own language as a tool and result of scientific knowledge in its connection with the peculiarities of the nature of knowledge and thinking. Changing scientific paradigms, increasing the level of abstractness of scientific theories, transforming the content of the objective category, the emergence of relativistic interpretations of scientific knowledge and, as a result, a departure from giving rationality the status of the only "scientific" form of mastering the world inevitably leads to a cardinal breakdown of "epistemological values" and a change in the holistic image of science in contemporary cultural space.
Keywords: metaphor; phenomenon; metalanguage of linguistics; metalinguistics